2009
DOI: 10.4049/jimmunol.0900842
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor IgE Adjuvanticity: Key Role of FcεRI

Abstract: Working with C57BL/6 mouse tumor models, we had previously demonstrated that vaccination with IgE-coated tumor cells can protect against tumor challenge, an observation that supports the involvement of IgE in antitumor immunity. The adjuvant effect of IgE was shown to result from eosinophil-dependent priming of the T cell-mediated adaptive immune response. The protective effect is likely to be mediated by the interaction of tumor cell-bound IgE with receptors, which then trigger the release of mediators, recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 45 publications
3
51
0
Order By: Relevance
“…We challenged both IgE-KO and matching wild-type (WT) mice by s.c. injection of TS/A tumor cells. After tumor cell engraftment, tumor volume progression in WT mice was comparable to that reported in a previous study (11) and identical to that observed in IgE-KO mice (Fig. 1A).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…We challenged both IgE-KO and matching wild-type (WT) mice by s.c. injection of TS/A tumor cells. After tumor cell engraftment, tumor volume progression in WT mice was comparable to that reported in a previous study (11) and identical to that observed in IgE-KO mice (Fig. 1A).…”
Section: Resultssupporting
confidence: 89%
“…To account for the dependence among longitudinal observations as well as for possible undetectable initial differences, tumor growth curves were estimated by an exponential mixed effect model with multiplicative errors: V(t) = a 0 e ait e, where V is the volume of the tumor at time t, e has log-normal distribution, and i is the experimental condition (11). The model was fitted by restricted maximum likelihood (19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations